LEGAL FRAMEWORK AND MECHANISMS TO COUNTER ABUSE IN THE SECURITIES MARKET IN IN THE CASE OF EUROPEAN UNION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article discusses the legal support, legal framework and mechanisms to counter abuse in the securities market in in the case of European Union. In order to protect the freedom and rights of parties of securities market, Government should regulate effectively by law. In article, the legal basis and mechanisms of the European Union in this field are analyzed.